Clinical efficacy and in vitro neutralization capacity of monoclonal antibodies for severe acute respiratory syndrome coronavirus 2 delta and omicron variants. Issue 10 (11th June 2022) - Brehm, Thomas Theo; Pfefferle, Susanne; von Possel, Ronald; Karolyi, Mario; Zoufaly, Alexander; Wichmann, Dominic; Kobbe, Robin; Emmerich, Petra; Nörz, Dominik; Aepfelbacher, Martin; Schulze zur Wiesch, Julian; Addo, Marylyn M.; et al.
Abstract: We aimed to provide in vitro data on the neutralization capacity of different monoclonal antibody (mAb) preparations against the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) delta and omicron variant, respectively, and describe the in vivo RNA kinetics of coronavirus disease 2019 (COVID‐19) patients treated with the respective mAbs. Virus neutralization assays were performed to assess the neutralizing effect of the mAb formulations casirivimab/imdevimab and sotrovimab on the SARS‐CoV‐2 delta and omicron variant. Additionally, respiratory tract SARS‐CoV‐2 RNA kinetics are provided for 25 COVID‐19 patients infected with either delta variant ( n = 18) or omicron variant ( n = 7) treated with the respective mAb formulations during their hospital stay. In the virus neutralization assay, sotrovimab exhibits neutralizing capacity at therapeutically achievable concentrations against the SARS‐CoV‐2 delta and omicron variant. In contrast, casivirimab/imdevimab had neutralizing capacity against the delta variant but failed neutralization against the omicron variant except for a very high concentration above the currently recommended therapeutic dosage. In patients with delta variant infections treated with casivirimab/imdevimab, we observed a rapid decrease of respiratory viral RNA at day 3 after mAb therapy. In contrast, no such prompt decline was observed in patients with delta variant or omicron variant infections receiving sotrovimab.